2013
DOI: 10.1158/1535-7163.mct-13-0123
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic Induction of Apoptosis in Multiple Myeloma Cells by Bortezomib and Hypoxia-Activated Prodrug TH-302, In Vivo and In Vitro

Abstract: Recently, we showed that hypoxia is a critical microenvironmental factor in multiple myeloma, and that the hypoxia-activated prodrug TH-302 selectively targets hypoxic multiple myeloma cells and improves multiple disease parameters in vivo. To explore approaches for sensitizing multiple myeloma cells to TH-302, we evaluated in this study the antitumor effect of TH-302 in combination with the clinically used proteasome inhibitor bortezomib. First, we show that TH-302 and bortezomib synergistically induce apopto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 47 publications
2
42
2
Order By: Relevance
“…For example, the hypoxia-activated prodrug TH-302 induces apoptosis in hypoxic myeloma cells either alone or in combination with bortezomib. 10 In line with this study, our results showed that auranofin-induced TrxR1 inhibition exerted an anti-proliferative effect on hypoxic RPMI8226 and U266 cells (Fig. 2).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…For example, the hypoxia-activated prodrug TH-302 induces apoptosis in hypoxic myeloma cells either alone or in combination with bortezomib. 10 In line with this study, our results showed that auranofin-induced TrxR1 inhibition exerted an anti-proliferative effect on hypoxic RPMI8226 and U266 cells (Fig. 2).…”
Section: Discussionsupporting
confidence: 88%
“…Our results complement another study that showed that TrxR1 inhibition by a similar auranofin concentration (1.5 mM) has increased the bortezomib sensitivity of human colon carcinoma cell line HCT116 overexpressing Bcl ¡ 2 by 2-fold under normoxic conditions. 40 While many therapies targeting the hypoxic myeloma cells are being developed either as a single agent or combinatorial therapies, 8,10 our study provided evidence that targeting hypoxic myeloma cells using TrxR1 inhibitors, such as auranofin, provides a potentially useful and novel treatment strategy for MM.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our findings provide reasons to use a combination of proteasome inhibitors and/or immunomodulatory drugs in addition to hypoxia-targeting drugs. 46 In conclusion, we have shown that KDM3A strongly correlates with HIF-1a dependence in myeloma cells after hypoxic exposure, contributing to the survival of hypoxia-subjected myeloma cells. KDM3A contributes to the maintenance of MALAT1 expression, which may lead to continuous HIF-1a expression during hypoxia.…”
Section: Discussionmentioning
confidence: 56%